Examen especial a la cuenta activos disponibles de la cooperativa de transportes central Catamayo, del cantón Catamayo, provincia de Loja, periodo 2013 - Barrera Criollo, Zoila Johana (2015)
Thispaper titledSPECIALCONSIDERATIONTO THE INCOMEASSETSAVAILABLEFORCOOPERATIVETRANSPORTCENTRALCATAMAYO, CANTONCATAMAYO, PROVINCEOF LOJA, PERIOD2013,itperformed asa prerequisiteto obtaining thetitle ofEngineerin Accounting and AuditingCPA., in whichthe knowledge acquiredin university classroomsis appliedin additionto the implementation ofspecialexaminationwould becontributingto theCooperativeCentralTransportCatamayo, togivea professionalopinion on theassetshasavailable, to have major importance becauseyour accountantmovement. For the realizationof thisresearch is toadvancethoseobjectiveswerefullymet; Cooperativefacilitiesmany timeswere necessary to obtainsufficient appropriateinformation leading tothe execution of thespecial examinationisvisited; theinternal control systemin order toexamine the riskand based on thesameselectthe necessary testsand thereforetake the most appropriatetechniques tocharacterize thereasonableness of transactionsandbalanceshave theaccountassetsareassessedAvailable infinancial statementwhose resultsareoutlined in the reportbythe conclusionsand recommendations. Theconclusions thatwere reachedafter the processthe specialreview is completedisto be consideredorganizing allthedocuments supportingtransactions,like itsimmediate registrationin the accounting systemthat managesthe Cooperative, also in relationdepositsas they are madedailyand managersto take steps torectifythis